Geology of the Pleistocene volcano of Monte Amiata (Southern Tuscany, Italy) - Claudia Principe; Luigina Vezzoli; Sonia La Felice (Journal of Maps)
Monte Amiata (305–231 ka; Italy) is an uncommon example of an entirely effusive silicic (mainly trachytic) composite volcano. A detailed geological map (1:25,000 scale) based on Unconformity Bounded Stratigraphic Unit criteria is presented accompanied by volcano-tectonic, stratigraphic relationship, and volcano evolution schemes. The volcanic facies analysis and structural analysis criteria have been applied to decipher Monte Amiata's geological evolution and structure, and to infer the relations between volcanism and regional tectonics. Based on the occurrence of a first-order geological unconformity representing a paleo-weathering surface of paleoclimatic significance, two major volcanic stratigraphic units and seven phases of activity are recognized.Highlights Monte Amiata is a volcano with the rare peculiarity of being completely silicic and effusiveThe produced, detailed, geological map has been the primary tool for the comprehension of the history of the volcano and will be the primary tool for land managementUsing of the Unconformity Bounded Stratigraphic Units hallowed us to reconsider Monte Amiata not as an isolated volcanic body but as a part of the geology of this portion of Southern Tuscany.At Monte Amiata, where the second largest Italian geothermal field is located, a complete geological picture means giving substantial help to geothermal resource development